Dynamics Of Election Supervision Authority By The Constitutional Court Of The Republic Of Indonesia After The Revision Of The Election Law: A Review Of Constitutional Law - Lestari, Sulistyani Eka; Tahir Yahya, Muhammad (KLAUSULA (Jurnal Hukum Tata Negara Adminitrasi Dan Pidana), 2025)
This study examines the changes in the Constitutional Court’s authority regarding election supervision and its implications for the principle of people’s sovereignty within Indonesia’s constitutional law system. The research adopts a normative legal method employing statutory, conceptual, and case approaches. The findings reveal that amendments through Law No. 7 of 2023 and Constitutional Court Regulation No. 4 of 2023 have expanded the Court’s authority beyond adjudicating election disputes to supervising electoral processes constitutionally. This expansion strengthens the protection of citizens’ voting rights but may disrupt the balance between judicial and administrative functions in a democratic framework. The implications for people’s sovereignty are ambivalent: while enhancing constitutional justice, it simultaneously risks transferring part of the people’s sovereign power to the judiciary. Thus, proportional authority, decision transparency, and institutional capacity strengthening are essential to ensure that the reform reinforces rather than undermines democratic sovereignty.